Monolithic Integrated Chip With SOA and Tunable DI for Multichannel All-Optical Signal Processing - Zhuyang Huang; Tong Cao; Liao Chen; Yu Yu; Xinliang Zhang (IEEE Photonics Journal, 2018)
An indium phosphide-based monolithic integrated chip with semiconductor optical amplifiers and a tunable delay interferometer (DI) is developed. Because of the comb filtering characteristics of DI, this chip has the potential to be used for multichannel all-optical signal processing functions in dense wavelength-division-multiplexed networks. In this paper, four-channel all-optical format conversion simultaneously from nonreturn-to-zero to return-to-zero at 40 Gb/s with a power penalty of less than 0.5 dB is demonstrated as a validation based on this chip.